Identifikasi Awal Wilayah Pengaruh KA Komuter Dengan Menggunakan Angkutan Umum Pengumpan - Anita Susanti; Ria Asih Aryani Soemitro; Hitapriya Suprayitno (Rekayasa Sipil, 2017)
The public perception that the quality of public transport service is very bad cause the number of private vehicle users is very high compared with the number of users of public transport. Therefore, an initial identification of the Commuter Train influence area by feeder is required. The goal is to know how big the area of the Commuter Train influence area viewed from the use of public transport feeder on the way to and leave the station. The method used in this initial identification is the collection of primary data by conducting interview survey of SUSI Commuter Train and the SULAM Commuter Train. Survey is conducted from two different directions in the morning departure hours only. The result of initial identification is known that the city of Surabaya has the Commuter Train influence area of SUSI Commuter Train and the SULAM Commuter Train 2 different directions in the morning departure hour by using feeder to the origin station of 9000 meters (20%) and from the destination station of 6000 meter (63.64%).